Dampak Kecelakaan Bus Wisata: Perspektif Perizinan dan Kelayakan untuk Keselamatan Transportasi - Ilham, Ilham (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
This study examines the impact of tourism bus accidents from the perspective of vehicle licensing and the feasibility of improving the safety and sustainability of public transportation. The findings show that the current licensing and surveillance system is still ineffective, with many tourist buses operating without valid permits and not undergoing periodic inspections. These indicate the need for regulatory framework reforms, including implementing stricter licensing standards and increased frequency of vehicle inspections. The study emphasizes the importance of collaboration between regulators and tourism stakeholders and the need for public awareness campaigns to improve regulatory compliance by strengthening the supervision mechanism and ensuring the roadworthiness of vehicles. These efforts reduce the risk of accidents and improve overall passenger safety.